El puño suena igual en todo el mundo: cantando el abuso doméstico en México y Tanzania - Rosenberg, Aaron Louis (El Colegio de México, 2015)
Domestic violence against women is an issue often concealed by the “culture of silence”. However, popular music has served as a powerful artistic expression to bring light to the issue in both public and active spaces. Mexico and Tanzania are two such examples. Therefore, a contrastive analysis is presented between two songs: Mexican song "Me golpeaste tanto anoche" and Tanzanian song "Kidogo Kidogo". For this purpose, the “inherent hypertextuality” theorical structure is applied, which allows linking works that respond to similar phenomena, as well as Judith Butler’s ideas on gender as a social construction. The aim is to understand the song’s techniques and the impact in promoting social awareness and battling ignorance and silent compliance to violence against women.